2023
DOI: 10.3390/microorganisms11051242
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Study of Combined Effect of Some Algerian Medicinal Plants and Probiotics against Helicobacter pylori

Bouhenni Hasna,
Hemida Houari,
Doukani Koula
et al.

Abstract: Helicobacter pylori causes gastritis, peptic ulcers and gastric cancer and affects more than half of the world’s population. Although this infection can have serious consequences, no novel cure or remedy have been discovered, the present therapy still relies on a variety of known antibiotics and anti-secretory agents. In the present study, the potential effect of combinations between methanolic extracts of four Algerian medicinal plants, garlic (Allium sativum), red onion (Allium cepa), cumin (Cuminum cyminum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 74 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…88 B. breve also demonstrated robust inhibitory effect on H. pylori in vitro and alleviated H. pylori-associated gastric inflammation in rats. 89 Thus, these findings imply that lactic acid bacteria Lactobacillus and Bifidobacterium have certain commonalities in antagonising H. pylori, which may be due to their production of lactic acid or competition for the binding sites on gastric epithelial cells.…”
Section: Beneficial Microbes Inhibit H Pylorimentioning
confidence: 87%
“…88 B. breve also demonstrated robust inhibitory effect on H. pylori in vitro and alleviated H. pylori-associated gastric inflammation in rats. 89 Thus, these findings imply that lactic acid bacteria Lactobacillus and Bifidobacterium have certain commonalities in antagonising H. pylori, which may be due to their production of lactic acid or competition for the binding sites on gastric epithelial cells.…”
Section: Beneficial Microbes Inhibit H Pylorimentioning
confidence: 87%
“…Hasna et al treated H. pylori with fenugreek extract and Bifidobacterium breve alone, and the highest IZD (inhibition zone diameter) was 16.00 ± 0.00 mm and 20.33 ± 0.58 mm, respectively. However, when the two drugs were combined to treat H. pylori, the Frontiers in Microbiology 13 frontiersin.org IZD was 28.67 ± 0.58 mm (Hasna et al, 2023). As a result, the combination began to be taken seriously.…”
Section: Immune Pathwaysmentioning
confidence: 99%
“…These trials mostly focused on triple therapy and showed enhanced eradication rates and decreased occurrence of adverse effects when it was used in combination with different probiotics (Wang et al, 2023a). There are many alternative eradication therapies based on probiotics as adjuvant agents (Penumetcha et al, 2021), such as the combination of multiple antibiotic-resistant lactic acid bacteria preparations and Vonoprazan (Kakiuchi et al, 2020), capsules containing four probiotics (Telaku et al, 2022) and combined mixtures of medicinal plants extracts with different probiotic strains (Hasna et al, 2023).…”
Section: Probiotics In Helicobacter Pylori Infectionmentioning
confidence: 99%